Effect of threshing, drying and storage methods on purity and germination of farmer managed rice seed in Uganda (Makerere University Journal of Agricultural & Environmental Sciences, 2004)
A total of seventy farmer-saved rice seed samples from three districts of Uganda namely Bugiri, Pallisa, and Lira were examined for purity and germination following procedures described by the International Seed Testing Association. The results revealed that postharvest handling practices (threshing, drying and storage) significantly (P
Keywords: Farmer-saved seed; postharvest; seed quality